Association between Epstein-Barr virus reactivation and severe malaria in pregnant women living in a malaria-endemic region of Cameroon. - Ide Armelle Djuidje Chatue; Maximilienne Ascension Nyegue; Severin Donald Kamdem; Franklin Maloba; Iqbal Taliy Junaid; Pawan Malhotra; Palmer Masumbe Netongo (Public Library of Science (PLoS), 2024)
Malaria kills nearly 619,000 people each year. Despite the natural immunity acquired to malaria, pregnant women and children under five die from severe forms of the disease in sub-Saharan Africa. Co-infection with acute Epstein-Barr Virus (EBV) infection has been shown to suppress the anti-malarial humoral responses, but little is known about the impact of EBV reactivation on malaria-associated morbidity. This study investigated the association between EBV reactivation and malaria severity in pregnant women living in a malaria-endemic region in Cameroon. A cross-sectional study was conducted on 220 pregnant women attending antenatal consultations in three health facilities in the West region of Cameroon. Malaria was diagnosed by microscopy, and Plasmodium species were identified by Nested PCR. Plasma samples were analyzed by ELISA for the presence of EBV nuclear antigen, EBV viral capsid antigen, and EBV early antigen to determine EBV reactivation. All statistics were performed using GraphPad Prism and SPSS software. The prevalence of malaria among pregnant women was 23.2%, of which 18.6% were P. falciparum mono-infections and 4.5% mixed infections (3.6% P. falciparum and P. malariae; 0.9% P. falciparum and P. ovale). 99.5% of the women were EBV seropositive, and 13.2% had EBV reactivation. Pregnant women with reactivated EBV were more likely to develop severe malaria than pregnant women with latent EBV (OR 4.33, 95% CI 1.08-17.25, p = 0.03). The median parasitemia in pregnant women with latent EBV was lower than in those with EBV reactivation (2816 vs. 19002 parasites/μL, p = 0.02). Our study revealed that lytic reactivation of EBV may be associated with the severity of malaria in pregnant women. Suggesting that, like acute infection, EBV reactivation should be considered a risk factor for severe malaria in pregnant women in malaria-endemic regions or could serve as a hallmark of malaria severity during pregnancy. Further detailed studies are needed.